When a pet dies - Rogers, Fred.; Judkis, Jim (New York : Putnam, 1988)
Explores the feelings of frustration, sadness, and loneliness that a youngster may feel when a pet dies.
Children's Catalog (Wilson)
School Library Journal
3.3
K-3
Keywords: Children and death -- Juvenile literature; Bereavement -- Juvenile literature; Pets -- Death -- Psychological aspects -- Juvenile literature; Pets -- Death; Death; Death; Pets